Dominant follicle removal by ultrasound guided transvaginal aspiration and superovulatory response in Nellore cows - Gradela, A. [UNESP]; Esper, Cesar Roberto [UNESP]; Matos, S.P.M.; Lanza, J.A.; Deragon, L.A.G.; Malheiros, R.M. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2000)
O presente estudo analisou o significado fisiológico do folículo dominante (FD) e sua remoção na resposta superovulatória de 42 vacas Nelore e testou a hipótese de que o número de folículos subordinados pequenos (3-8mm) poderia ser usado como critério único para a avaliação da presença ou ausência de um FD nos ovários. Exames ultra-sonográficos foram realizados dois dias antes do início do tratamento superovulatório (D0) e as vacas foram divididas em três grupos: grupo sem FD (SFD), grupo com FD (FD) e grupo com um FD aspirado (FDA). A resposta superovulatória das doadoras não diferiu entre os grupos, mas a taxa de viabilidade embrionária foi maior nos grupos SFD (69,40%) e FDA (68,99%) grupos, comparados ao FD (48,54%). O número de estruturas não fertilizadas não diferiu entre os grupos SFD e FD nem entre SFD e FDA, mas foi maior no grupo FD comparados ao FDA. Pode-se concluir que, em vacas Nelore, a determinação do número de folículos subordinados é um critério seguro para a avaliação da presença ou ausência de um FD nos ovários, mas erros poderiam ser evitados se apenas folículos de 4-8mm fossem considerados, e que a presença de um FD no início da superovulação reduz a taxa de viabilidade embrionária e sua remoção por aspiração transvaginal guiada por ultra-som induziu taxas de viablidade embrionárias semelhantes àquelas observadas na ausência de um FD.

The present study analyzed the physiological significance of the dominant follicle (DF) and its removal on the superovulatory response of 42 Nellore cows and tested the hypothesis that the number of subordinate small follicles (3-8mm) could be used as a single criterion for the evaluation of the presence or absence of a DF in the ovaries. Ultrasonographic examinations were performed two days before the beginning of superovulatory treatment (D0) and the cows divided into three groups: group without DF (NDF), group with a DF (DF) and group with an aspirated DF (ADF). The superovulatory response of the donors did not differ between groups, but the rate of embryonic viability was higher in NDF (69.40%) and ADF (68.99%) groups compared to DF (48.54%). The number of unfertilized structures did not differ between NDF and DF or between NDF and ADF groups, but was higher in DF compared to ADF. It is concluded that, in Nellore cows, the number of subordinate follicles is a safe criterion for the evaluation of the presence of a DF in the ovaries, but errors could be avoided if only 4-8mm follicles were considered, and that the presence of a DF at the beginning of superovulation reduced the embryonic viability rate and its removal by transvaginal aspiration guided by ultrasound induced embryonic viability rates similar to that observed in the absence of a DF.
Remoção do folículo dominante por aspiração transvaginal guiada por ultra-som e reposta superovulatória em vacas Nelore
Keywords: Bovino; Nelore; aspiração do folículo dominante; resposta superovulatória; Bovine; Nellore; dominant follicle aspiration; superovulatory response